Leishmania Parasites Drive PD-L1 Expression in Mice and Human Neutrophils With Suppressor Capacity - da Fonseca-Martins, Alessandra M.; de Souza Lima-Gomes, Phillipe; Antunes, Maísa Mota; de Moura, Renan Garcia; Covre, Luciana P.; Calôba, Carolina; Rocha, Vivian Grizente; Pereira, Renata M.; Menezes, Gustavo Batista; Gomes, Daniel Claudio Oliveira; Saraiva, Elvira M.; de Matos Guedes, Herbert L. (Frontiers in Immunology, 2021)
Neutrophils play an important role in the outcome of leishmaniasis, contributing either to exacerbating or controlling the progression of infection, a dual effect whose underlying mechanisms are not clear. We recently reported that CD4+ and CD8+ T cells, and dendritic cells of Leishmania amazonensis-infected mice present high expression of PD-1 and PD-L1, respectively. Given that the PD-1/PD-L1 interaction may promote cellular dysfunction, and that neutrophils could interact with T cells during infection, we investigated here the levels of PD-L1 in neutrophils exposed to Leishmania parasites. We found that both, promastigotes and amastigotes of L. amazonensis induced the expression of PD-L1 in the human and murine neutrophils that internalized these parasites in vitro. PD-L1-expressing neutrophils were also observed in the ear lesions and the draining lymph nodes of L. amazonensis-infected mice, assessed through cell cytometry and intravital microscopy. Moreover, expression of PD-L1 progressively increased in neutrophils from ear lesions as the disease evolved to the chronic phase. Co-culture of infected neutrophils with in vitro activated CD8+ T cells inhibits IFN-γ production by a mechanism dependent on PD-1 and PD-L1. Importantly, we demonstrated that in vitro infection of human neutrophils by L braziliensis induced PD-L1+ expression and also PD-L1+ neutrophils were detected in the lesions of patients with cutaneous leishmaniasis. Taken together, these findings suggest that the Leishmania parasite increases the expression of PD-L1 in neutrophils with suppressor capacity, which could favor the parasite survival through impairing the immune response.